Evaluation of Abrasion and Whitening Effect of Toothpastes Containing Charcoal on Primary Teeth - Masoud Fallahinejad Ghajari; Maryam Shamsaei; Maedeh Sadeghpour Galouyak; Kimia Basandeh (Tehran University of Medical Sciences, 2022)
Objectives: Parents are aware of the importance of anterior tooth esthetics in their children. Children also pay attention to their appearance more than ever. Today, charcoal has been added to toothpastes. This study aimed to investigate the degree of bleaching and abrasion of charcoal toothpaste on primary teeth. Materials and Method: This in-vitro study was performed on 30 extracted primary teeth. Initially, the samples were polished, cut, and mounted in blocks of putty. The samples were placed in a coffee solution and then the tooth color was measured by a spectrophotometer and the initial surface profile was measured by a profilometer. The samples were brushed back and forth by the brushing machine with 20 gr Bancer, Beverly, and Colgate toothpastes (mixed with 40 ml of distilled water) for 2000 times (equivalent to 3 times a day for 1.5 months). A color determination was performed again and a second surface profile was measured. The data were analyzed by one-way ANOVA, ANCOVA and paired t-test. Results: The results of this study showed that all three Beverly, Bencer and Colgate whitening toothpastes increased the surface profile and made significant statistical changes in the roughness of dental specimens (P=0.01, P=0.005, P=0.001). The statistical study of the data did not show a significant difference between the groups in terms of abrasion and whitening properties (P=0.78, P= 0.99). Conclusion: Three whitening toothpastes whiten primary teeth and increase their surface roughness. These three toothpastes are not statistically different in terms of abrasion and whitening properties.